2007
DOI: 10.1586/14737159.7.5.519
|View full text |Cite
|
Sign up to set email alerts
|

CpG islands: their potential as biomarkers for cancer

Abstract: In general, DNA methylation acts in concert with other epigenetic processes, including histone modifications, chromatin remodeling and microRNAs, to shape the overall chromatin structure of the nucleus and potentially modify its functional state. Aberrant DNA methylation events can occur in a number of human diseases but we are only just beginning to appreciate the scope and magnitude of this process in human health. As one example, in contrast to normal cells, the cancer methylome is characterized by reciproc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 99 publications
(60 reference statements)
2
42
0
Order By: Relevance
“…Lastly, epigenetic events can interact with several cell cycle regulators (Chuang et al, 1997). Deregulated gene expression via DNA methylation has also been recognized as a key factor of aging (Qureshi and Mehler,in press) and many kinds of pathologies (Shi et al, 2007). To date, DNA methylation is emerging as functions in not only cancer but also neurological, cardiovascular (Frey, 2005), and immunological diseases (Shi et al, 2007;Esteller, 2006).…”
Section: Dna Methylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, epigenetic events can interact with several cell cycle regulators (Chuang et al, 1997). Deregulated gene expression via DNA methylation has also been recognized as a key factor of aging (Qureshi and Mehler,in press) and many kinds of pathologies (Shi et al, 2007). To date, DNA methylation is emerging as functions in not only cancer but also neurological, cardiovascular (Frey, 2005), and immunological diseases (Shi et al, 2007;Esteller, 2006).…”
Section: Dna Methylationmentioning
confidence: 99%
“…Deregulated gene expression via DNA methylation has also been recognized as a key factor of aging (Qureshi and Mehler,in press) and many kinds of pathologies (Shi et al, 2007). To date, DNA methylation is emerging as functions in not only cancer but also neurological, cardiovascular (Frey, 2005), and immunological diseases (Shi et al, 2007;Esteller, 2006). In the following sections, we will discuss what is known about DNA methylation changes in lung cancer and how these alterations are applied potentially to diagnosis and prognosis of the disease.…”
Section: Dna Methylationmentioning
confidence: 99%
“…35 It has been shown that DNA methylation in different body fluids reflects the methylation patterns found in primary tumors. 130 For example, methylation of the p16…”
Section: Epigenetic-targeted Therapy In Oncologymentioning
confidence: 99%
“…Thus, aberrant methylation of the promoters of a number of genes shows great promise as biomarkers for early detection (11,12 ) and predicting prognosis (13)(14)(15)(16)(17). Furthermore, tumor-derived circulating DNA from apoptotic cancer cells can often be detected in the serum and other body fluids obtained from can-cer patients (18 ).…”
Section: © 2009 American Association For Clinical Chemistrymentioning
confidence: 99%